Pengaruh Kerjasama Tim, Pengembangan Karir Dan Pelayanan Sidik Jari Pembuatan Skck Luar Negeri Terhadap Kepuasan Kerja Dengan Variabel Intervening Komitmen Organisasional Pada Inafis Polda Jawa Tengah - Astutik, Dwi; Adijati, Adijati; Kuswardhani, Kuswardhani (Universitas 17 Agustus 1945 Samarinda, 2025)
Identification is something that is very mandatory for the front guard in processing crime scenes at the Central Java Regional Police Investigation, especially in making a police record certificate (SKCK). This identification is known as INAFIS (Indonesia Automatic Finger Print Identification System). The duties of employees in the INAFIS unit require high levels of foresight and accuracy. Therefore, employee job satisfaction in the INAFIS unit needs to be considered. This research aims to analyze the influence of teamwork, career development and service on employee job satisfaction at the INAFIS unit of the Central Java Regional Police with Organizational Commitment as an intervening variable. This research analysis uses a quantitative data analysis technique using a questionnaire to collect the required primary data through a questionnaire method. The sample in this study was 148 which was obtained through the proportional simple sampling method, where all populations have the same opportunity to be selected as samples. The analysis used to process the data is multiple regression analysis using SPSS software. The results of this research show that only career development and service have a significant effect on the level of organizational commitment. Teamwork, career development and service have a significant effect on the level of job satisfaction, while organizational commitment does not significantly influence job satisfaction. The findings in this study reveal that organizational commitment mediates the effect of service on job satisfaction.